Ligand-controlled Regiodivergent C-H Alkenylation of Pyrazoles and its Application to the Synthesis of Indazoles - Kim, Hyun Tae; Ha, Hyeri; Kang, Geunhee; Kim, Og Soon; Ryu, Ho; Biswas, Abul Kalam; Lim, Sang Min; Baik, Mu-Hyun; Joo, Jung Min (John Wiley & Sons Ltd., 2017)
Regioselective C4-, C5-, and di-alkenylations of pyrazoles were achieved. An electrophilic Pd catalyst generated by trifluoroacetic acid (TFA) and 4,5-diazafluoren-9-one (DAF) leads to C4-alkenylation, whereas KOAc and mono-protected amino acid (MPAA) ligand Ac-Val-OH give C5-alkenylation. A combination of palladium acetate, silver carbonate, and pivalic acid affords dialkenylation products. Annulation through sequential alkenylation, thermal 6 pi-electrocyclization, and oxidation gives functionalized indazoles. This comprehensive strategy greatly expands the range of readily accessible pyrazole and indazole derivatives, enabling useful regiodivergent C-H functionalization of pyrazoles and other heteroaromatic systems.
Keywords: AMINO-ACID LIGANDS; DIRECT ARYLATION; ACTIVATION; FUNCTIONALIZATION; OXIDATION; MECHANISM; INDOLES; ARENES; AZOLES; ROUTE